GEOMETRIC ARRANGEMENT PLAN ON 3 STREETS IN BAFRA DISTRICT (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2022)
The population of Bafra district, located in the west of Samsun province, is approximately 150,000. A geometric arrangement plan has been made at the intersections of Cumhuriyet Street, Ishakli Street and Yaka Cami Street in Bafra district, which is located on an area of 175 km2. Along with the geometric arrangement plan, horizontal vertical marking plates were also designed at these intersections. Before the regulations, traffic counts were made at the intersections and the streets were monitored with camera images. In addition, one-way and two-way traffic directions of the streets have also been rearranged.